Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai (Studi Pada Puskesmas Tulung Selapan Kabupaten Ogan Komering Ilir) - ., Alviona; Roni, Mukran; ., Trisninawati; Septayuda, Irwan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study is motivated by the suboptimal performance of employees, reflected in their inability to complete daily service tasks effectively, as well as issues of work motivation characterized by low attendance discipline. The purpose of this research is to analyze the effect of leadership style and work motivation on employee performance at Puskesmas Tulung Selapan. The study employs a quantitative approach using a survey method by distributing questionnaires to 72 employees selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The findings reveal that both leadership style and work motivation have a positive and significant influence on employee performance. These results underscore that enhancing leadership effectiveness and providing appropriate motivation can improve employee productivity and performance quality.